Contribution of benthic microalgae to ice covered coastal ecoystems in northern Hokkaido, Japan - Andrew McMinn; Hirawake, T; Hamaoka, T; Hattori, H; Fukuchi, M (2005)
Benthic microalgal communities usually make a major contribution to the primary production of estuaries and shallow seas. Pulse amplitude modulation (PAM) fluorometry was used to investigate the contribution of benthic microalgae to the primary production of the Okhotsk Sea coast and Saroma Ko Lagoon in northern Hokkaido. In general the benthic communities had a relatively high biomass but low photosynthetic activity. This led to estimates of 29.2% and 64.5% for the benthic contributions for the 9 m and 3 m depth sites at Mombetsu and 13.1% for Saroma Ko. Sea ice algae provided the greatest contribution at Saroma Ko.